The Relationship Between Science Process Skills and Critical Thinking of Grade IV Students in East Ungaran District - Fasha Faradilla Rosa; Ela Suryani (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Science process skills (SPS) and critical thinking are essential competencies in elementary science education; however, multi-school evidence concerning their relationship among fourth-grade students remains limited. This study examined the relationship between SPS and critical thinking among fourth-grade students attending public elementary schools in East Ungaran, Indonesia. A quantitative correlational design was employed, involving 105 students selected through cluster sampling from four schools. Data were collected from May to June 2025. SPS was assessed using six process indicators, whereas critical thinking was measured using five categories adapted from Ennis’s framework. Instrument trials involving 22 fifth-grade students yielded reliability coefficients of .715 for SPS and .794 for critical thinking. Data were analyzed using SPSS 26 through normality, homogeneity, linearity, and Pearson product–moment correlation tests. The data satisfied the reported assumptions, including normality (p = .065) and linearity (deviation from linearity, p = .125). The results revealed a positive, statistically significant relationship between SPS and critical thinking (r = .601, p < .001, N = 105), representing approximately 36.1% shared variance. Thus, stronger science process skills were associated with higher critical-thinking performance. This study contributes multi-school correlational evidence concerning the relationship between these competencies and supports elementary science instruction that explicitly integrates observation, interpretation, prediction, questioning, communication, and evidence-based reasoning.